Spatio‐temporal patterns in the woodiness of flowering plants - Ao Luo; Xiaoting Xu; Yunpeng Liu; Yaoqi Li; Xiangyan Su; Yichao Li; Tong Lyu; Dimitar Dimitrov; Markku Larjavaara; Shijia Peng; Yongsheng Chen; Qinggang Wang; et al. (Global Ecology and Biogeography, 2023)
Aim Woody and herbaceous habits represent one of the most distinct contrasts among angiosperms, and the proportion of woody species in floras (i.e., “woodiness” hereafter) represents a fundamental structural element of plant diversity. Despite its core influence on ecosystem processes, spatio‐temporal patterns in woodiness remain poorly understood. Here, we aim to demonstrate the global spatio‐temporal patterns in angiosperm woodiness and their relationship with environmental factors. Location Global. Time period Cenozoic, 66 Ma to present. Major taxa studied Angiosperms. Methods Using newly compiled data on the growth forms and distributions of c . 300,000 angiosperm species and an angiosperm phylogeny, we mapped the current global geographical patterns in angiosperm woodiness, reconstructed ancestral states of growth forms through the angiosperm phylogeny and demonstrated the Cenozoic evolutionary dynamics of woodiness. We evaluated the relationships between woodiness and current climate and palaeoclimate. Results We found that c . 42.7% of angiosperms are woody. Woodiness decreased spatially from the equator towards high latitudes, temporally since the early Cenozoic. Temperature was the best predictor of the spatio‐temporal decline in woodiness and was positively correlated with woodiness. Despite the temporal decline in woodiness, macroevolutionary herbaceous‐to‐woody transitions increased through time and contributed to the evolution of woody floras in temperate drylands, whereas the opposite transitions decreased through time and contributed to herbaceous floras in tropical and subtropical drylands. Main conclusions Our study improves understanding of the spatio‐temporal dynamics of angiosperm woodiness. Our findings suggest that temperature is likely to be a determinant of spatio‐temporal variations in woodiness, highlighting the role of temperature in maintaining the growth form composition of ecosystems. Our study also calls for attention to growth form transitions (e.g., secondary woodiness) in temperate drylands that have been neglected before.